2020
DOI: 10.14744/turkpediatriars.2020.82997
|View full text |Cite
|
Sign up to set email alerts
|

Child healthcare system in Ukraine

Abstract: The child healthcare system in Ukraine is coordinated and managed at a central level by the Ministry of Health and at a local level by the regional health authorities. The Ministry of Health has executive the power for the implementation of state health policies and controls and manages state-owned health facilities. The system of public funding for the pediatric healthcare system is divided into two sources: central and local. Primary healthcare is organized by the National Health Service of Ukraine. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 1 publication
0
28
0
2
Order By: Relevance
“…The healthcare system in Ukraine is divided into the national level, which is administered by the Ministry of Health, and several regional levels. 72 Less than 1 in 20 Ukrainians are covered by voluntary private medical insurance. 72 In 2014, the Central Intelligence Agency World Factbook stated that there were 2.99 physicians and 7.5 hospitals beds per 1000 residents in Ukraine.…”
Section: Healthcare System and Population Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The healthcare system in Ukraine is divided into the national level, which is administered by the Ministry of Health, and several regional levels. 72 Less than 1 in 20 Ukrainians are covered by voluntary private medical insurance. 72 In 2014, the Central Intelligence Agency World Factbook stated that there were 2.99 physicians and 7.5 hospitals beds per 1000 residents in Ukraine.…”
Section: Healthcare System and Population Healthmentioning
confidence: 99%
“…72 Less than 1 in 20 Ukrainians are covered by voluntary private medical insurance. 72 In 2014, the Central Intelligence Agency World Factbook stated that there were 2.99 physicians and 7.5 hospitals beds per 1000 residents in Ukraine. 114 About 1% of the adult population in Ukraine had the human immunodeficiency virus (HIV) or acquired immune deficiency syndrome (AIDS) in 2020, which ranked it number 45 in the world.…”
Section: Healthcare System and Population Healthmentioning
confidence: 99%
“…The results of the bibliometric analysis confirmed the increasing interest of the scientists to analyse of the pandemic issues not only from the medical issues [1][2][3] but also from the social, ecological and economic points of views [4][5][6][7][8][9][10][11][12][13]. Besides the vulnerableness of the world under the coronavirus requires the developing of the effective instruments to overcome the recession after the lockdowns.…”
Section: Introductionmentioning
confidence: 68%
“…The third cluster analysed the factors and determinants, which influenced on the pandemic consequences spreading and extending. In the paper [2] the scientists allocated the age as the main factor which influenced the virus penetrating. The fourth cluster (yellow) showed that the scientists analysed the linking between pandemic and air pollutions, climate change, health risks etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in the previous research and the author'sanalysis of the ways and experience of solving similar organizational andmethodological problems have identified the need for structural and logicalsystematization and their generalization for the sound development of structural-functional model (SFM) medical care for children 0-3 years old with bronchopulmonal dysplasia (BPD) and children of older age groupsdysplastic dependent pathologyofbroncho-pulmonal system (BPS) [1][2][3][4][5][6][7][8] . The urgency of suchdevelopment is conditioned by the existing socio-medical significance of the problem of health preservation 4,[9][10][11] , first of all prematurely born children with low andlow body weight, high levels of their disability and morbidity 5-8; 12-17 .This publication describes the elaborated regulatory acts on the introduction of health technologies in SFM 18 .…”
Section: Introductionmentioning
confidence: 99%